Children with COVID-19 Who Manifest Febrile Seizure - Lilia Dewiyanti; Neni Sumarni; Joseph Deni Lie; Zuhriah Hidajati; Harancang Pandih Kahayana; Adriana Lukmasari; Cipta Pramana (Case Reports in Medicine)
The COVID-19 pandemic is a challenge for all medical personnel in the world. Various studies have been conducted to gain more knowledge about SARS-CoV-2, but studies in the pediatric population are still very limited. We report a case of a boy aged two years and seven months who came to the hospital with an atypical generalized seizure for less than 5 minutes and immediately regained consciousness after the seizure. Other symptoms included fever, productive cough, rhinorrhea, and shortness of breath. The X-ray showed a well-defined homogeneous consolidation in the upper right lobe and a small spot in both lungs which consistently showed top right lobar pneumonia and bronchopneumonia. From the SARS-CoV-2 nucleic acid test, positive results were obtained on the third day of hospitalization. The patient received antiseizure therapy, antibiotics, and other supportive therapies by Indonesian Pediatrician Association (IDAI) guidelines. During treatment, the patient responded well to the treatment given, with no other seizure episodes. A negative result on the SARS-CoV-2 nucleic acid test was obtained after twelve days of hospitalization as well as improvements of the lungs as seen from the X-ray.